Peningkatan kemampuan representasi matematis siswa melalui model pembelajaran berbasis inkuiri berbantuan software geogebra - Panjaitan, Alchairunnisa; Siregar, Tanti Jumaisyaroh (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2024)
The students' inadequate mathematical representation abilities, as seen by their trigonometry learning outcomes, are the driving force for this investigation. This study aims to determine whether using Geogebra software in combination with an inquiry-based learning approach may improve students' mathematical representation skills. Of the seventy students enrolled at SMA Negeri 1 Ketambe, twenty-five students from class X IPA 1 and twenty-five students from class X IPA 2 were assigned to the experimental and control courses, respectively. The second class used a quasi-experimental technique with a pre- and post-test design. Tests used as research instruments. The data analysis methods that were employed were the N-Gain Test, Normality Test, Homogeneity Test, and T-Test. The results of the study on hypothesis testing indicate that an inquiry-based learning model can enhance students' capacity for mathematical representation, and that students who employed this strategy saw higher gains in this capacity than those who received conventional instruction.